Business Ethics and the ‘End of History’ in Corporate Law - Heath, Joseph (Journal of business ethics, 2011)
Henry Hansmann has claimed we have reached the “end of history” in corporate law, organized around the “widespread normative consensus that corporate managers should act exclusively in the economic interests of shareholders.” In this paper, I examine Hansmann’s own argument in support of this view, in order to draw out its implications for some of the traditional concerns of business ethicists about corporate social responsibility. The centerpiece of Hansmann’s argument is the claim that ownership of the firm is most naturally exercised by the group able to achieve the lowest agency costs, and that homogeneity of interest within the ownership group is the most important factor in achieving lower costs. He defends this claim through a study of cooperatives, attempting to show that homogeneity is the source of the competitive advantage most often enjoyed by shareholders over other constituency groups, such as workers, suppliers and customers, when it comes to exercising control over the firm. Some business ethicists, impressed by this argument, have taken it to be a vindication of Milton Friedman’s claim that profit-maximization is the only “social responsibility” of management. I would like to suggest that this conclusion does not follow, and that the “Hansmann argument” lends itself to a less minimalist view, what I refer to as a “market failures” approach to business ethics.